2017
DOI: 10.1186/s41065-017-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Microarray study of gene expression profile to identify new candidate genes involved in the molecular mechanism of leptin-induced knee joint osteoarthritis in rat

Abstract: BackgroundOsteoarthritis (OA) is one of the most prevalent chronic joint diseases while the precise genetic mechanism remains elusive. In this study, we investigated the gene expression profile in OA by microarray analysis.ResultsHistopathological characteristics of OA cartilage were examined using a rat model of leptin-induced OA. Gene expression profile of leptin-induced articular cartilage and healthy rat cartilage were compared using genome-wide microarray hybridization. A total of 1857 genes differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Additionally, Ob‐Rb is expressed in chondrocytes and is functional (Figenschau et al ., ). Recently, a microarray analysis associated the leptin‐induced OA phenotype with the up‐regulation of inflammatory factors, MMPs, growth factors and osteogenic genes (Fan et al ., ). Our group has demonstrated that leptin, in synergy with IL‐1β, induces the expression of pro‐inflammatory factors, including NOS2, COX‐2, PGE 2 , IL‐6 and IL‐8 (CXCL8) in chondrocytes (Gomez et al ., ).…”
Section: Leptin and Osteoarthritismentioning
confidence: 97%
“…Additionally, Ob‐Rb is expressed in chondrocytes and is functional (Figenschau et al ., ). Recently, a microarray analysis associated the leptin‐induced OA phenotype with the up‐regulation of inflammatory factors, MMPs, growth factors and osteogenic genes (Fan et al ., ). Our group has demonstrated that leptin, in synergy with IL‐1β, induces the expression of pro‐inflammatory factors, including NOS2, COX‐2, PGE 2 , IL‐6 and IL‐8 (CXCL8) in chondrocytes (Gomez et al ., ).…”
Section: Leptin and Osteoarthritismentioning
confidence: 97%
“…However, most of the studies reported a catabolic role of leptin underlying OA pathogenesis. A recent study determining the gene expression profile of leptin-induced articular rat cartilage by microarray analysis, associated the up-regulation of matrix metalloproteinases (MMPs), inflammatory factors, growth factors and osteogenic genes with leptin-induced OA phenotype ( Fan et al, 2018 ). Our group demonstrated that leptin (400 or 800 nM), in synergy with IFNγ or IL-1β, activated type 2 nitric oxide synthase (NOS2) via JAK2, PI3K and MAPK (MEK1 and p38) pathways, in cultured human and murine chondrocytes ( Otero et al, 2003 , 2005 , 2007 ).…”
Section: Leptin and Immune-metabolic Pathologiesmentioning
confidence: 99%
“…Moreover, DNA methylation in OA chondrocytes correlates with leptin expression [103], which associates with the BMI [96]. Fan et al reported different genes associated with the leptin-induced OA phenotype in rats by microarray analysis, including genes related to MMPs, inflammatory factors, growth factors, apoptosis, and osteogenesis [104].…”
Section: Leptinmentioning
confidence: 99%